Impairment of respiratory function in late‐onset distal myopathy due to MATR3 Mutation. Issue 6 (June 2015) - Kraya, Torsten; Schmidt, Bernd; MüLLER, TOBIAS; Hanisch, Frank
ABSTRACT Introduction: Recently, mutations in the MATR3 gene were found to cause late‐onset distal myopathy. The frequency and impact of respiratory involvement are not clear. Methods: Respiratory parameters [maximum vital capacity (VCmax); forced expiratory volume (FEV1); peak expiratory flow (PEF), postural drop of VCmax from sitting to supine, maximum inspiratory muscle pressure (PImax), mouth occlusion pressure after 100 ms (P 0.1), peak cough flow, and blood‐gas analysis] were monitored prospectively at baseline, and then 6 months and 12 months later in 8 patients with genetically confirmed MATR3 myopathy. Results: All patients showed involvement of respiratory function. Six of 8 reported exertional dyspnea. At the end of follow‐up, 5 of 8 had decreased VC, 7 of 8 had reduced PImax, and 5 of 7 had decreased partial pressure of oxygen (PO2). Within 12 months, respiratory parameters deteriorated non‐significantly. No patient required non‐invasive ventilation. Conclusions: There is a high risk of abnormal respiratory function with progressive worsening in MATR3 myopathy. Muscle Nerve51: 916–918, 2015